First discovery of the genus Discothyrea Roger, 1863 (Hymenoptera: Formicidae: Proceratiinae) from Sumatra, Indonesia - Satria, Rijal; Jannatan, Robby; Syukria Hayati Musfira,; Rafi, Mahesa; Gusti, Meliana; Halimah Tus Sakdiah,; Dwi Hilda Putri, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2022)
We herein report Discothyrea clavicornis Emery, 1897 from three localities of West Sumatra, as the first record of the genus from the island. This species was collected from the leaf-litter layer of the lowland and highland disturbed forests in West Sumatra Province.